PERANCANGAN APLIKASI KEAMANAN FILE AUDIO FORMAT WAV (WAVEFORM) MENGGUNAKAN ALGORITMA RSA - Santoso, Heri; M. Fakhriza, M. Fakhriza (Universitas Islam Negeri Sumatera Utara, 2018)
WAV file is a standard format that is widely used in multimedia and games on various platforms. Ease of access and development of technology with various media making it easier to exchange information to various places. Both important and confidential data need to be kept confidential because of various security threats so that data can be tapped and known by third parties during the submission process. One method of data security is cryptography using a public key algorithm that is poluler is RSA (Rivest Shamir Adleman). From these problems raised the idea to create a data security application whose function can perform data security using RSA algorithm. The programming language used is C # with Visual Studio software, the data being processed is a sample of each byte in a WAV file, the header will be the same as the beginning so that the WAV file can be played even if the information is disguised. RSA algorithms can be implemented into programming languages so that WAV files can be processed and secured data. Although the results of WAV file size after encryption becomes larger depending on the key used by existing information can be disguised properly.